Implementasi Alih Media Sertifikat Tanah ke Sertifikat Elektronik oleh PPAT Kota Tangerang Selatan untuk Mendukung Reforma Agraria - Maulidiana, Amalia Rahma; Deni, Fitra; Wijaya, Endra (CV. Social Politic Genius (SIGn), 2025)
Modernizing land administration through e-certificates is imperative to strengthen Indonesia’s legal certainty of land rights. This research aims to analyze the factual implementation of the E-certificate media conversion mechanism by Land Deed Making Officials in South Tangerang City following the enactment of Ministerial Regulation Number 3 of 2023, examine the legal certainty of its product, and evaluate its contribution as a supporting instrument for Agrarian Reform. Employing an empirical legal approach with qualitative analysis through interviews and document study, this study finds that the initial implementation of media conversion by Land Deed Making Officials faced significant dynamics and operational challenges related to system and procedural readiness, requiring intensive adaptation. Nevertheless, e-certificates from media conversion possess a strong foundation of normative legal certainty and have gained widespread practical recognition, especially from the banking sector, as Electronic Mortgage Right collateral. Further evaluation indicates that this media conversion implementation factually supports modern Agrarian Reform’s objectives, primarily through enhancing the guarantee of legal certainty. However, early implementation barriers still constrain its full administrative efficiency and transparency potential. It is concluded that media conversion is a fundamental supporting instrument for Agrarian Reform in the digital era. However, realizing its optimal benefits requires system maturation and stakeholders’ continuous resolution of implementation challenges.